The Influence of Tax Knowledge and Taxpayer's Attitude To Public Awareness in Paying Land and Urban and Rural Land Tax - Maristiana Ayu (Saburai International Journal of Social Sciences and Development, 2017)
Land and Rural Land and Urban Tax (PBB P2) is a very potential tax and strategy as a source of state income in order to finance the implementation of government in development. With the payment of the UN Tax P2 as an important revenue source in the development of each region for it needs government efforts through raising taxpayers' awareness in paying taxes, because the success of tax revenue is a reflection of public awareness. This study aims to analyze the influence of knowledge taxation and attitudes of taxpayers to public awareness in paying PBB P2. The data obtained are primary data with questionnaires distributed in four sub-districts from nine sub-districts in Pringsewu District. Sample selection method in this study by purposive sampling technique. Test results in research indicate that knowledge of taxation have a significant positive effect to public awareness in paying PBB P2, whereas attitudes of taxpayers have no significant effect on public awareness in paying taxes. And together knowledge and attitude of the taxpayer affect the public awareness in paying PBB P2.